Clinical significance of indeterminate pulmonary nodules in patients with locally advanced head and neck squamous cell carcinoma. Issue 3 (1st June 2013) - Alford, Raphael E.; Fried, David V.; Huang, Benjamin Y.; Weissler, Mark; Shores, Carol; Shockley, William; Hackman, Trevor; Zanation, Adam; Hayes, Neil; Weiss, Jared; Grilley–Olson, Juneko; Jewells, Valerie; et al.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to determine whether indeterminate pulmonary nodules (IPNs) at staging are predictive of lung metastasis, primary lung carcinoma, or survival in patients with advanced head and neck squamous cell carcinoma (HNSCC). Methods One hundred ten patients with IPN at staging who had follow‐up imaging and 100 patients without IPN were identified from an HNSCC database. The primary endpoints were lung progression‐free survival (PFS) and overall survival (OS). Results Two‐year lung PFS for the IPN and No‐IPN cohorts were 66% versus 61% (p = .92) and the OS for these cohorts were 71% versus 68% (p = .77). Within the IPN cohort, level IV/V lymph node involvement (odds ratio = 4.34; p = .03), hypopharynx primary (odds ratio = 21.5; p = .005), and race (odds ratio = 9.29; p = .001) were independent predictors of developing lung malignancy. Conclusion IPNs at staging in patients with HNSCC do not affect prognosis and should neither influence initial treatment planning nor the frequency of posttreatment surveillance. © 2013 Wiley Periodicals, Inc. Head Neck36: 334–339, 2014